Architecture, Art, and Memory: Tracing Ceramic Panels in Denizli - Elifcan Duygun; Saniye Fışgın Korkmaz (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
This study is the first detailed record of architectural ceramic panels in Denizli, Çamlık, offering important information about how architecture and ceramic design come together. Although architectural-artistic cooperation has been thoroughly investigated in major cities such as Istanbul, Ankara, and Izmir, research in regional contexts is scarce. This study examines the ceramic creations of Mehmet Tüzüm Kızılcan and Fatma Ilgın Şekerci, evaluating their contributions through archival material, site visits, and direct interviews. Furthermore, this study questions the broader impact and prevalence of architecture-art collaborations beyond major urban centers. The research highlights the societal changes in Denizli, especially the evolving urban landscape of Çamlık, where these artistic interventions are integrated. Beyond aesthetics, these panels reflect historical and social dynamics, marking shifts in architectural discourse. By bridging modernist architectural trends with traditional motifs, these works enrich the visual identity of public and residential spaces.